Knee Osteoarthritis in Women: Ancient and Modern Treatment Modalities (AYUSHDHARA, 2024)
Knee osteoarthritis (OA) is a common and debilitating condition that predominantly affects women. This article explores the historical and contemporary treatment modalities for knee OA in women, highlighting the evolution of therapeutic approaches over time. Ancient treatments for knee OA primarily focused on natural remedies and lifestyle modifications. These included the use of herbal medicines, dietary adjustments, and physical therapies like hot and cold compresses. Ancient cultures recognized the importance of maintaining a healthy weight and engaging in physical activity to alleviate symptoms and improve joint function. In modern times, treatment options for knee OA in women have significantly evolved. While conservative measures such as physical therapy, weight management, and non-steroidal anti-inflammatory drugs (NSAIDs) are still important, advanced interventions are available. These include corticosteroid injections, hyaluronic acid injections, and platelet-rich plasma therapy, which aim to reduce pain and enhance joint lubrication. For severe cases, surgical interventions like arthroscopy, partial or total knee replacement, and osteotomy may be considered. The article also explores the emerging field of regenerative medicine, which offers promising avenues for the management of knee OA in women. Stem cell therapies and tissue engineering approaches show potential in regenerating damaged cartilage and slowing down disease progression. Additionally, the role of lifestyle modifications, exercise, and physical therapy remains crucial in the modern era, with a focus on tailored rehabilitation programs to improve strength, flexibility, and joint stability. In conclusion, the treatment of knee OA in women has transitioned from ancient remedies rooted in tradition to a modern, evidence-based approach that combines conservative measures with innovative medical interventions. The evolution of treatment modalities reflects advances in medical knowledge and technology, offering hope for improved quality of life for women affected by this condition.